Increasing Incidence of Hypertension in Females: A Study in Islamabad,Pakistan - Tajamal, Nasira; Tajamal, Maryam; Tajammal, Salman; Tajammal, Rehan (International Journal of Innovative Research in Medical Science, 2019)
The incidence of hypertension in both males and females were studied in patients coming to the medical center of OGDCL Islamabad. Patients were selected between the ages of 45 and 60 years. Three blood pressure readings were recorded on their consecutive visits. WHO suggested grading for hypertension was used to classify the patients in three categories, Body mass index[BMI] was used to define obesity and overweight. Waist Hip Ratio[WHR] was measured to distinguish between upper and lower body type obesity. Total number of patients screened was 847. Males were 458 and females were 389. Hypertensive patients were 320 and among these 320 hypertensive patients 176 were women; while male were144. Females already on antihypertensive drugs were 80 and 192 males were already on antihypertensive drugs. 208 women were obese[BMI above 30] and 32 were overweight[BMI above 25]. 48 males were obese while 16 were overweight. In women the upper body type obesity was found in 192 patients; while in males upper body type obesity was in 32 patients. The cases excluded from the study were diabetics, patients with secondary hypertension, patients with proteinuria, polycystic renal disease, patients with IHD, stroke and MI.